2021
DOI: 10.1186/s12912-021-00765-2
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of factors influencing treatment engagement among patients with cardiovascular diseases: a systematic review

Abstract: Background Nurses are key to the success of patient engagement, yet we know little about nurses’ perceptions on treatment engagement and how they can contribute to treatment engagement. Qualitative evidence to identify factors that influence treatment engagement among patients with CVD from nurse’s perspective is limited. Methods This systematic review of qualitative research was based on the PRISMA reporting guidelines. The Joanna Briggs Institute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Healthcare professionals were considered the most important source of information, followed by consultation with the internet. Providing information from healthcare professionals, particularly nurses, can support patients effectively and reinforce treatment adherence [ 42 , 43 ]. Chemotherapy patients often preferred to base their decisions on the recommendations of their care providers and required adequate information retention.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals were considered the most important source of information, followed by consultation with the internet. Providing information from healthcare professionals, particularly nurses, can support patients effectively and reinforce treatment adherence [ 42 , 43 ]. Chemotherapy patients often preferred to base their decisions on the recommendations of their care providers and required adequate information retention.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between health professionals and patients is one factor that is known to affect medication adherence. Successful communication between healthcare providers and patients promotes greater patient satisfaction with medical care, strengthening medication adherence [27]. However, a lack of family support was reported as a significant contributing factor to non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study conducted by Ahmed et al ( 2022 ) found that nurses had multiple barriers to practice cardiac rehabilitation such as organisational-related barriers, for example, a lack of financial resources, a lack of training about acute phase of cardiac rehabilitation, shortages of staff members, a lack of specific protocols or policies to address phase 1 of cardiac rehabilitation, and a lack of supervision. In addition, a study conducted by Rashidi, Whitehead and Kaistha ( 2021 ) found that the nurses perceived the lack of time to engage the patients in their treatment plan impacted their ability to provide quality care to patients.…”
Section: Introductionmentioning
confidence: 99%